PENGARUH PERAN GANDA, BEBAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA KARYAWAN(Studi Kasus Pada Perawat Wanita di RS Harum Sisma Medika) - Khofifa Khairunisa, (2022)
This research is a quantitative study that aims to determine and prove the effect of multiple roles, workload and organizational commitment on the job satisfaction of female nurses at Harum Sisma Medika Hospital. The sample used in this study was 45 married female nurses at Harum Sisma Medika Hospital, with the sampling technique using saturated sampling. The tests used were the coefficient of determination test, t test and f test using the help of the SmartPLS 4.0 program. The test results obtained are (1) multiple roles have a positive and significant effect on job satisfaction (2) workload has a positive and significant effect on job satisfaction (3 organizational commitment has a positive and significant effect on job satisfaction (4) multiple roles, workload and commitment organizational work simultaneously influences the job satisfaction of female nurses at Harum Sisma Medika Hospital.